Proyecto de abastecimiento de agua para irrigar 280 hectáreas de frutales en el lateral 7a- 78 Irrigación Chavimochic. Fundo Vibuvisa. Chao. La Libertad - Cuba Rodriguez, Henry Luis (2011)
At the present time, as the avocado orchards and vines, are highly profitable, but until now Peru is in a constant struggle to get export more agricultura! products to overseas market. Avocado and Vine have a good acceptance in the European market, has now gotten the Peruvian avocado enter the U. S. market. Thus, the production of avocado and Vine was bom as an interesting altemative business, considering all the health virtues, which are very consistent with changing consumer trends in both U. S. and European Union. This project seeks to determine the technical and economic feasibility of establishing an orchard of 280 acres of Hass avocado and vine variety Reg Glo be in the valley of Chao. This enhancement project drip irrigation, this type of project, have a high cost, even considering high investrnent costs. To achieve a good quality product develops a study of the· Chao valley in their growing conditions, conditions and characteristics of the soils, presence of labor demanded by the project, the items and cultivated species in the area, and so on. On the other hand, develops a presentation of technical study and Hass avocado variety Vid Red Globe, in terms of characteristics and conditions that these crops require. Furthermore, it becomes an econornic study ofthe project, which presents the necessary resources for its development and management, analysis of price and volume of avocados and grapes sold in the intemational rnarket, based on these results, price projections are and volurnes that were used to determine the incorne generated by the project are profitability indicators IRR and NPV as well as a sensitivity analysis. On the other hand, develops a technical presentation of Hass avocado variety and study Vid Red Globe, in terrns of Characteristics and conditions These crops require That. Furthermore, it Becornes an Econornic Study of the project, Which presents the resources for ITS NECESSARY Developrnent and Managernent, analysis of price and volurne of avocados and grapes sold in the intemational rnarket, based on results These, price and volurnes are Projections That Were Used to determine the Incorne generated by the project are IRR and NPV Profitability Indicators as well as a sensitivity analysis